Streamflow estimation at ungauged site using wavelet group method of data handling in Peninsular Malaysia [electronic resource] - Basri Badyalina, 1989- author (2014)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2014